Cutaneous onchocerciasis in Dumbu, a pastoral area in the North-West region of Cameroon: diagnostic challenge and socio-economic implications - Njim, Tsi (Pan Afr Med J, 2015)
Onchocerciasis is a severe parasitic infestation caused by Onchocerca volvulus which causes disabling skin and subcutaneous tissue changes and ultimately leads to blindness. It has a huge public health impact due to its socioeconomic burden and the vast number of people it affects in developing countries. In this case, a 60 years old woman was encountered with leopard skin like changes, rashes and pruritus on the left leg; which had been managed as cutaneous mycosis for over a period of 8 years. A diagnosis of onchocerciasis was finally made after a skin snip identified onchocercal microfilariae. The above case shows that onchocerciasis is still a neglected tropical disease (NTD) in Cameroon. This emphasizes the need for more expansive outreach programs in remote areas in Cameroon, a change in health policies to ensure the eradication of this disabling disease and health promotion amongst vulnerable populations.